Peningkatan Kejujuran Akademik pada Mahasiswa melalui Pelatihan Pendidikan Anti Korupsi - Putri, Putri Pusvitasari; Heryadi, Adi; Puspitasari, Dian (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2024)
Students may indeed be seen as not committing acts of corruption at all with state funds, but the violations they commit are irresponsibility for what has been entrusted to them, especially in an academic context. If positioned equally, conditions like this have the potential to cause students to commit the same acts of corruption as public officials. Based on this problem, a special intervention or treatment is needed to improve student academic honesty, one of which is anti-corruption education training. This research aims to see how effective anti-corruption education training is in improving academic honesty in students. The research method used was an experiment with the target subjects being 22 active students of the Psychology Study Program Unjani Yogyakarta. The experimental design used in this research is One Group Pretest Posttest Design, where there is only 1 group of subjects, namely the experimental group. Based on the results of data analysis through the paired sample t test, a significance value of 0.000 was obtained (p < 0.05). This means that there is a very significant difference before and after the anti-corruption education training given to the training participants.